Enseñar Historia en Venezuela: carencias, tensiones y conflictos - Inés Quintero (Caravelle)
In Venezuela since the elaboration of the first textbooks in the nineteenth century until today, History’s teaching has been part of an important process including discussion and reflection about the contents and the adopted didactic strategies. This paper aims to review the fundamental aspects concerning the deficiencies and recurring problems in History’s teaching and to analize the tensions and conflicts brought about by study options and contents related to Venezuelan History in the textbooks, formulated and distributed by the actual Venezuelan government.